Cover Feature: Adduct of NacNacAl with Benzophenone and Its Coupling Chemistry (Chem. Eur. J. 1/2020). Issue 1 (13th November 2019) - Dmitrienko, Anton; Britten, James F.; Spasyuk, Denis; Nikonov, Georgii I.
Abstract : Like the docking of two space‐ships : The adduct of NacNacAl with benzophenone easily couples with unsaturated substrates. The phenyl ring of benzophenone acts like a switch that opens the port, while the aluminum atom and the α‐carbon are the beacons orienting the incoming molecule. Such a communication between the building blocks of the adduct enables selective coupling with high yields of the products. The scope of substrates includes aldimine, quinoline, phenyl nitrile, trimethyl azide, and a saturated cyclic thiourea. More information can be found in the Full Paper by G. I. Nikonov et al. on page 206 .